Maritime navigation and radiocommunication equipment and systems. Shipborne automatic transponder system installation using VHF digital selective calling (DSC) techniques. Operational and performance requirements, methods of testing and required test results Part 1, (15th August 2001) - British Standards Institution,
No abstract available